Perceptions on teleworking among potential employees in private organizations in Kuala Lumpur - Wan Mohd Rani, Wan Nurul Mardiah; Kadar Hamsa, Abdul Azeez (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
The main focus of this paper is primarily to investigate the perception towards teleworking with relation to the basic travel characteristics. To achieve the aim of study, general and basic travel characteristics were analysed together with the perceptions lmvards teleworking and the preference to practice teleworking. This paper is structured with three main sections, which cover status of teleworking in Malaysia, status of teleworking in other countries such as Japan, United States, United Kingdom and Singapore and finally the exploration of the study itself.